Achieving sustainability of greenhouses by integrating stable semi-transparent organic photovoltaics - DEĞER, CANER; YAVUZ, İLHAN (My University, 2023)
Semi-transparent organic photovoltaics (OPVs) are an emerging solar-energy-harvesting technology with promising applications, such as rooftop energy supplies for environmentally friendly greenhouses. However, the poor operational stability of OPVs poses challenges to their feasibility as incessantly serving facilities. Here we report a reductive interlayer structure for semi-transparent OPVs that improves the operational stability of OPVs under continuous solar radiation. The interlayer effectively suppresses the generation of radicals from the electron transport layer under sunlight and prevents the structural decomposition of the organic photoactive layer during operation. The defects that serve as the charge carrier recombination sites are nullified by the electron-donating functional groups of the reduced molecules, which improves photovoltaic performance. The semi-transparent OPVs demonstrate a power conversion efficiency of 13.5% and an average visible transmittance of 21.5%, with remarkable operational stability (84.8% retention after 1,008 h) under continuous illumination. Greenhouse results show that the semi-transparent OPV roof benefits the survival rate and growth of the crops, indicating the importance of our approach in addressing food and energy challenges.
Keywords: Sosyal ve Beşeri Bilimler; Coğrafya; Sosyoloji; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Çevre Mühendisliği; Çevre Teknolojisi; Ekoloji ve Kirlenme; Jeofizik Mühendisliği; Gıda Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Geography; Sociology; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Environmental Engineering; Environmental Technology; Ecology and Pollution; Geophysical Engineering; Food Engineering; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Sosyal Bilimler (SOC); Tarım Bilimleri; Çevre / Ekoloji; Mühendislik; Yerbilimleri; Sosyal Bilimler Genel; GIDA BİLİMİ VE TEKNOLOJİSİ; ÇEVRE BİLİMLERİ; EKOLOJİ; ENERJİ VE YAKITLAR; COĞRAFYA; JEOKİMYA VE JEOFİZİK; KENTSEL ÇALIŞMALAR; ÇEVRE ÇALIŞMALARI; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Social Sciences (SOC); AGRICULTURAL SCIENCES; ENVIRONMENT/ECOLOGY; ENGINEERING; GEOSCIENCES; SOCIAL SCIENCES, GENERAL; FOOD SCIENCE & TECHNOLOGY; ENVIRONMENTAL SCIENCES; ECOLOGY; ENERGY & FUELS; GEOGRAPHY; GEOCHEMISTRY & GEOPHYSICS; URBAN STUDIES; ENVIRONMENTAL STUDIES; Küresel ve Gezegensel Değişim; Fizik Bilimleri; Yemek bilimi; Yaşam Bilimleri; Coğrafya, Planlama ve Geliştirme; Sosyal Bilimler ve Beşeri Bilimler; Ekoloji; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Kentsel çalışmalar; Doğa ve Peyzaj Koruma; Yönetim, İzleme, Politika ve Hukuk; Global and Planetary Change; Physical Sciences; Food Science; Life Sciences; Geography, Planning and Development; Social Sciences & Humanities; Ecology; Renewable Energy, Sustainability and the Environment; Urban Studies; Nature and Landscape Conservation; Management, Monitoring, Policy and Law